Converging Grammars : Constructions in Singapore English. - Ziegeler, Debra (Language Contact and Bilingualism LCB., 2015)
This volume provides a much-needed, critical overview of the field of constructions and construction grammar in the context of Singapore English, and poses the question of identifying a construction in contact when the lexicon is derived from one language and the syntax from another. Case studies are illustrated in which the possibility of a 'merger'-construction is offered to resolve such problems. The book is intended for students of construction theories, variation studies, or any researcher of contact grammars.